Trimetazidine reduces contrast-induced nephropathy in patients with renal insufficiency undergoing coronary angiography and angioplasty: A systematic review and meta-analysis (PRISMA) - Heshmatzadeh Behzadi, Ashkan (Medicine (Baltimore), 2021)
OBJECTIVES: This systematic review and meta-analysis assesses the utility of trimetazidine (TMZ) to prevent contrast induced nephropathy (CIN) in patients with renal insufficiency undergoing coronary angiography and angioplasty. MATERIALS AND METHODS: This meta-analysis was formulated and reported according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. A search of databases was conducted by 2 researchers independently for clinical trials, comparing hydration plus TMZ vs conventional hydration alone for prevention of CIN through January 2020. All patients had renal insufficiency (defined as GFR < 89 ml/minute/1.73 m(2)) and the outcome of interest was the incidence of contrast induced acute kidney injury. The odds ratio (OR) was estimated with 95% confidence interval (CI). Heterogeneity was reported with the I(2) statistic, using a fixed-effects model, and >50% of I(2) was considered to be statistically significant. RESULTS: Eleven studies, 1611 patients, met the inclusion/exclusion criteria: 797 patients comprised the TMZ plus hydration group and the remaining 814 patients comprised the control (hydration only) group. Heterogeneity was low I(2) = 0%, P = .84, and the heterogeneity of each study was also low. The incidence of CIN in the TMZ plus hydration group was 6.6% (53/797), while the incidence of CIN in the control (hydration only) group was 20% (165/814). Pooled analysis of all studies showed TMZ reduced incidence of CIN compared to saline hydration alone (OR risk 0.30, 95% CI 0.21, 0.42, P < .0001). CONCLUSION: TMZ added to hydration reduces CIN in renal insufficiency patients undergoing coronary angiography.